The ultimate encyclopedia of tennis the definitive illustrated guide to world tennis - Parsons, John; Wancke, Henry (Carlton Books, 2006)
The Ultimate Encyclopedia of Tennis is the pre-eminent single volume illustrated work of tennis reference, tracing the game from its relaxed beginnings as a pastime of the 1800s through to what has become the high energy global sport of the 21st century. John Parsons' celebrated book includes comprehensive chapters profiling the legends of the game and more than 150 top players; analysis of tennis's greatest matches; world famous tournaments and global development; as a well as extensive features on the politics, controversies and oddities of the game. Packed with around 200 photographs and complete with a record of all Grand Slam winners, every player, every tournament and every issue of importance in the game of tennis is highlighted in detail in the book. Written by two of the game's leading authorities, The Ultimate Encyclopedia of Tennis is the definitive work on world tennis, with every page an information-packed celebration of one of the world's most exhilarating sports.